Uma análise marcuseana da educação formal no Brasil: razão tecnológica e sociedade unidimensional - Louvrier, Lidia Aurea do Nascimento (2023)
This research aims to investigate the Brazilian public education system, focusing on the Reform of Secondary Education which was elaborated in 2016 according to the Provisional Measure 746/2016 and approved in 2017 in the terms of the Law 13.415/2017. Such reform promotes flexibility in the secondary education curriculum, consequently breaking down the traditional teaching model in the last stage of Brazilian formal public education, and has been implemented from 2022 in several schools across the country. We interpret this reform and its consequences following the philosophical theory of Herbert Marcuse (1898-1976), German philosopher and thinker, one of the great exponents of the cultural revolutions that occurred at the end of the 20th century. We assume as a theoretical basis Marcuse’s 1964 book “The ideology of industrial society”, which results from his extensive research on American society’s organization based on the advanced capitalist mode of production, and from that book we extract two concepts which are fundamental to the proper understanding of our proposal: technical rationality and unidimensionality, the first functioning as a condition for the development of the second. Although Marcuse has never privileged us with an actual education theory, it is possible to extract from his work through the criticism he launched against capitalist society and its institutions, even if in an underlying way, the problem of education. We then proceed from this theoretical assumption to understand the advancement of neoliberal policies in Brazilian education, which, according to our thesis, is consolidated with the New Secondary Education [Novo Ensino Médio - NEM].